Political and Public Policy Challenges in Addressing the National Debt Burden and New Tax Policies in Indonesia 2025 - Taufikurrahman; Nurlinah Nurlinah; Suhardiman Syamsu (al-Afkar, Journal For Islamic Studies, 2026)
2025 will be a crucial phase for Indonesia in maintaining fiscal sustainability amidst the increasing need for development financing and new tax policies, particularly the adjustment of the Value Added Tax (VAT) rate to 12% and the planned implementation of a carbon tax. This situation occurs when the government debt ratio is approaching 40% of GDP, thus creating political challenges as well as demands for effective public policy. This study aims to analyze the political dynamics accompanying the implementation of the new tax policy and public policy strategies in managing the national debt burden sustainably. The research method used is qualitative with a descriptive-analytical approach through literature studies, analysis of official documents (the 2025 State Budget, Financial Notes, tax regulations), and interviews with key informants. The results show that the success of fiscal consolidation in 2025 depends on three main factors: (1) the design of a selective VAT policy that takes into account aspects of social justice and purchasing power protection, (2) credible debt management through fiscal rule discipline and fiscal risk transparency, and (3) political legitimacy built through public communication and social compensation. The conclusion of this study confirms that the new tax policy can only be effective if supported by political stability, central-regional coordination, and an inclusive communication strategy. These findings are expected to provide academic and practical input in formulating Indonesia's fiscal policy in the consolidation era.